Hukum Pernikahan Beda Agama menurut Ulama Indonesia - Wiwin Siti Aminah; Roby Awaludin; Irfan Hilmi (Istinbath | Jurnal Penelitian Hukum Islam, 2020)
Marriage is one of the Sunnatullah which generally applies to all creatures of God, both in humans, animals, and plants. By doing a marriage someone will be protected from the temptations of Satan, both temptations from eyesight and genitals or lust. As the Messenger of Allah has ordered us to marry the person we like by giving them several considerations including his property, his beauty, his offspring, and especially in considering his religious problems. In the modern era, there are now many interfaith marriage practices, especially in Indonesia. With such problems, it is necessary to take legal conclusions relating to interfaith marriages.